Molecular stiffness cues of an interpenetrating network hydrogel for cell adhesion. (June 2022) - Li, Bin; Çolak, Arzu; Blass, Johanna; Han, Mitchell; Zhang, Jingnan; Zheng, Yijun; Jiang, Qiyang; Bennewitz, Roland; Campo, Aránzazu del
Abstract: Understanding cells' response to the macroscopic and nanoscale properties of biomaterials requires studies in model systems with the possibility to tailor their mechanical properties and different length scales. Here, we describe an interpenetrating network (IPN) design based on a stiff PEGDA host network interlaced within a soft 4-arm PEG-Maleimide/thiol (guest) network. We quantify the nano- and bulk mechanical behavior of the IPN and the single network hydrogels by single-molecule force spectroscopy and rheological measurements. The IPN presents different mechanical cues at the molecular scale, depending on which network is linked to the probe, but the same mechanical properties at the macroscopic length scale as the individual host network. Cells attached to the interpenetrating (guest) network of the IPN or to the single network (SN) PEGDA hydrogel modified with RGD adhesive ligands showed comparable attachment and spreading areas, but cells attached to the guest network of the IPN, with lower molecular stiffness, showed a larger number and size of focal adhesion complexes and a higher concentration of the Hippo pathway effector Yes-associated protein (YAP) than cells linked to the PEGDA single network. The observations indicate that cell adhesion to the IPN hydrogel through the network with lower molecular stiffness proceeds effectively as if a higher ligand density is offered. We claim that IPNs can be used to decipher how changes in ECM design and connectivity at the local scale affect the fate of cells cultured on biomaterials. Graphical abstract: Image 1 An interpenetrating network (IPN) of a stiff PEGDA host network interlaced within a soft 4-arm PEG-Mal/thiol (guest) network is designed to study the cell response to the macroscopic and nanoscale mechanical properties of the IPN hydrogel. The results indicate that cell adhesion to the IPN hydrogel through the network with lower molecular stiffness proceeds effectively as if a higher ligand density is offered.